Mudarabah Contract in The Property Investment: Critical Legal Review - Novira, Nuraeni; Sam, Zulfiah; Sarah, Sarah; Shoaleha, Mar'atu (Indonesian Journal of Islamic Economic Law, 2025)
This research aims to find out how the legality of the mudarabah system based on Law No. 21 of 2008 and how the implementation of mudarabah contracts in property investment. To get answers to the above problems, the author uses descriptive qualitative research (library research), which focuses on manuscript and text studies using normative, juridical and historical approach methods with deductive data analysis. The results show that legally, the mudarabah system has been regulated in Law No. 21 of 2008 through Articles 19 and 20 related to the collection and distribution of funds by Islamic banks. However, the implementation of mudarabah contracts in property investment has not fully complied with the provisions of the law, especially in the aspects of profit-sharing transparency (Article 21 letter b), risk monitoring (Article 26), and dispute resolution mechanisms (Article 55). This finding theoretically confirms the strength of the Islamic Banking Law in distinguishing partnership-based contracts from the conventional interest-based system. Practically, the implementation of mudarabah contracts in accordance with sharia principles can increase customer trust and loyalty, while non-compliant implementation has the potential to reduce the credibility of Islamic financial institutions.